Shelf-Life Feasibility Study of Moringa oleifera Seasoned Beef - Florence Adwoa Ayirezang; Reuben Essel Arhin; Barry Kojo Whyte; Emmanuel Opoku Antwi; Belinda Nana Ama Boateng (Journal of Food Quality)
This study explored the stability of beef treated with Moringa oleifera ethanolic leaves extract (MELE) stored at 4°C for 10 days. Beef samples were treated with MELE concentrations of 8%, 4%, and 2%. A 3% NaCl-treated beef sample and control were included. Samples were taken every 48 hours for microbiological analysis. The Nordic Committee on Food Analysis methods were used to determine the mesophilic, coliform, Staphylococcus aureus, Escherichia coli, and Salmonella sp. enumeration. The organoleptic properties were tested using the 5-point scale hedonism. There was a significant difference (p < 0.05) in the mean mesophilic and coliform counts, which varied from 2.0 × 103 ± 0.0 to 8.9 × 107 ± 0.4 CFU/ml and 1.0 × 101 ± 0.1 to 8.9 × 104 ± 0.3 CFU/ml, respectively, from storage day two to ten when beef treated with MELE was compared to the 3% NaCl and the control. Staphylococcus aureus grew on all the beef samples across all the different incubation periods, but a dose-dependent antibacterial activity of the M. oleifera-treated beef was observed for S. aureus with the maximum inhibition recorded for 8% MELE. Beef seasoned with MELE was free of E. coli throughout storage. Salmonella sp. was not detected in all the beef samples. Microbial loads increased with decreasing concentrations of MELE. The overall acceptability of MELE-treated beef decreased with increasing concentration of MELE treatment. MELE may find application in food preservation. The probability of synergistic activity of salt and M. oleifera leaves extract can be explored in further studies.